Metabolic profiling of target organic acids in Parkinson’s Disease using LC-ESI-MS - Karg, Rowan (Student Undergraduate Research E-journal!, 2019)
To date, the exact cause of Parkinson’s disease (PD) is still unclear. Therefore, detection of newer targets which can be linked to the pathogenesis or progression of PD is vital. In this study, liquid chromatography-electrospray ionization-mass spectrometry was used (LC-ESI-MS) to detect target organic acid metabolites. In addition, metabolite levels were determined in three cell lines namely a healthy control, gene-corrected PD and PINK1 mutant PD cell line. Several acids were successfully detected and results showed elevated levels of citric- and propanoic acid in the PINK1 mutant PD cell line compared to control groups. Further method improvement however is still necessary.